Can Simulation Improve EMR Implementation? Application to Medication Reconciliation. Issue 1 (June 2017) - Kazi, Sadaf; Khunlertkit, Adjhaporn; Chen, Allen
Medication reconciliation refers to the process of using multiple sources of information to identify the most accurate list of all medications a patient is taking, and using this list to provide correct medications to the patient for the current setting of care (Centers for Medicare & Medicaid Services [CMS], 2014, Institute for Safe Medication Practices [ISMP], 2005; Institute for Healthcare Improvement [IHI], 2017). Although there is considerable research on perceptions about medication reconciliation and opportunities to improve the process, there is a need to use objective measures to understand how this definition is interpreted by providers. We used a simulation study to investigate the process of performing medication reconciliation with oncology providers in an academic medical center. Contrary to our hypothesis we found that rather than the broad medical category of the medication (cancer-related vs. non-cancer condition vs. supplements), providers were more likely to elicit details about medications that were newly added to the electronic medical record. We discuss implications in terms of system redesign and patient safety.